GIỚI THIỆU PHƯƠNG PHÁP QUY TRÌNH XÁC LẬP, PHÂN VÙNG GIỚI HẠN TRƯỢT LỞ Ở SƯỜN DỐC CẤU TẠO TỪ ĐẤT ĐÁ KHÔNG ĐỒNG NHẤT DỌC ĐƯỜNG GIAO THÔNG VÙNG MIỀN NÚI - Lý, Nguyễn Đức; Thanh, Nguyễn; Hiên, Lê Thị Thúy (Vietnam Journal of Earth Sciences, 2011)
Processes for identification and zoning of landslide stability for lithologically heterogenous slopes along rural mountainous roads Landslide on slopes and talus (here after namely as slope) is a sophisticated geohazard which adversely affects all the aspects of socio-economic, environmental and livelihood development. In order to mitigate possible damages, the identification and zoning of landslide stability for lithologically heterogenous slopes in moutainous areas is of significant importance. In this paper, we would like to introduce the latest method on identification and zoning of landslide stability for lithologically heterogenous slopes in moutainous roads.